BERBAGI KREATIVITAS VISUAL: PELATIHAN DASAR VIDEOGRAFI DAN EDITING UNTUK STAF HUBUNGAN MASYARAKAT MUSEUM BAHARI - Kusumawati, Dyah; Delliana, Santi (BESIRU : Jurnal Pengabdian Masyarakat, 2024)
A community service program has been designed with the main aim of introducing the basic concepts of videography to public relations staff at the Maritime Museum, while also promoting tourism promotion. Through this training, participants will be given an in-depth understanding of the stages of video production, from pre-production to post-production, as well as basic techniques in shooting, composition and editing using editing applications. It is hoped that the participants will have sufficient skills to create interesting and informative visual content for the promotion of the Maritime Museum as an attractive tourist destination. Hopefully this program can also expand the reach and increase public interest in visiting the Maritime Museum, thereby contributing to the development of local tourism. This program combines practical training with promotional objectives, forming a solid foundation for increasing knowledge and skills while also promoting the beauty and uniqueness of the Maritime Museum as a tourist attraction worth visiting. Thus, this program not only supports the development of participants' skills, but also plays an active role in strengthening the image and tourist attraction of the city of Jakarta.